Silence : empowering women since late 1300’s - Tan, Joey Xue Ting (2016)
This Final Year Project explores the empowering impact silence can have when consciously wielded by women. Considering that such a tool has been used from Greek Tragedies to Science Fiction novels, this essay thus uses such a framework to explore how Geoffrey Chaucer similar empowers his female characters in The Canterbury Tales in Fourteenth Century Medieval England.